Mendelian randomization and single-cell expression analyses identify the causal relationship between depression and chronic rhinosinusitis - Zhou, Fangwei; Yang, Yan; Li, Jianyao; Jin, Ying; Zhang, Tian; Yu, Guodong (Frontiers in Psychiatry, 2024)
The causative relationship between chronic rhinosinusitis (CRS) and depression remains unclear. Herein we employed Mendelian randomization (MR) coupled with single-cell analysis to investigate the causality between CRS and depression.Methods: Data pertaining to CRS and depression were mined from the genome-wide association study database, and a single-cell dataset was sourced from the literature.To explore causality, we conducted bidirectional MR analysis using MR-Egger, weighted median, inverse variance weighted (IVW), simple mode, and weighted mode, with IVW representing the most important method. Further, sensitivity analysis was performed to evaluate the robustness of MR analysis results. Candidate genes were analyzed via single-cell combined MR analysis.Results: Forward MR analysis indicated depression as a risk factor for CRS when depression was the exposure factor and CRS was the outcome (OR = 1.425, P < 0.001). Reverse MR analysis revealed the same positive relationship between CRS and depression when CRS was the exposure factor and depression was the outcome (OR = 1.012, P = 0.038). Sensitivity analysis validated the robustness of bidirectional MR analysis results. Ten cell types (endothelial, ciliated, basal, myeloid, mast, apical, plasma, glandular, fibroblast, and T cells) were identified in the single-cell dataset.The network of receptor-ligand pairs showed that in normal samples, cell-cell interactions were present among various cell types, such as epithelial, mast, myeloid, and endothelial cells. In contrast, CRS samples featured only one specific receptor-ligand pair, confined to myeloid cells. TCF4 and MEF2C emerged as potentially crucial for CRS-associated depression development.Our findings suggest a bidirectional causal relationship between CRS and depression, offering a new perspective on the association between CRS and depression.